Estrategias de comunicación interna para la empresa Automotores de la Sierra (ASSA) – Ciudad de Ambato - Arias Toaza, Lizeth Estefanía (2024)
This project focuses on implementing a manual that contributes to internal communication for employees of the company ASSA Automotores de la Sierra, and implementing platforms where graphic pieces can be displayed that contribute to the external public having more information about the products. products and services offered by the establishment, ensuring that all material, whether digital or printed, remains consistent. ASSA is located in Ambato (headquarters) and has 17 branches nationwide. When companies have achieved a great positioning within the market, the situation may arise that their brand assets such as logo, colors, typography, among others, lose coherence. This establishment considers it extremely important that both the external and internal public correctly perceive each of its brand assets. Regarding the project, the problem is addressed using the inductive-deductive method, in addition to a qualitative and quantitative approach, by implementing information collection techniques such as interviews and surveys, in order to know the current situation presented by the assets of the company. brand and its mode of use. The results obtained revealed that the company has a high positioning in the minds of consumers at the province level, however, due to different situations in the country, the automotive sector has had declines, especially in the province. By implementing strategies that keep employees better informed and trained, they will be able to provide a better and excellent service to the external public, since as a result of the surveys it was found that the intangible asset that consumers value most is good service and it is followed by experience at the dealership, apart from the tangible ones such as the confessionals showing their products and their offers.